Sonographic Evaluation of Site Specific Nerve Dimensions in Young Asymptomatic Adults: A Cross-sectional Study - Sanjula Singh; Archana Rani; Garima Sehgal; Jyoti Chopra; Anita Rani; Manjula Singh; Kumari Pooja (International Journal of Anatomy Radiology and Surgery, 2022)
Introduction: Tibial Nerve (TN) and Common Peroneal Nerve (CPN) supply the muscles and skin of lower extremity via their major branches and also send articular branches to the joints of lower extremity. Knowledge of nerve dimensions is useful for diagnosis of pathologies, planning nerve blocks, biopsies or other therapeutic procedures. Aim: To assess bilateral Tibial Nerve (TN) and Deep Peroneal Nerve (DPN) morphology and morphometry at ankle through a sonographic evaluation. Materials and Methods: A cross-sectional, observational study was conducted in the Department of Anatomy, King George’s Medical University, Lucknow, Uttar Pradesh, India from September 2018 to August 2019. Morphology and morphometry of TN and DPN was observed by High Resolution Ultrasonography (HRUS) at specific anatomical site in 100 first year Bachelor in Medicine and Bachelor in Surgery (MBBS) students (50 males and 50 females). The nerve parameters like, Cross-sectional Area (CSA), nerve perimeter and depth from skin were measured and the data was analysed statistically. Among asymptomatic subjects, various nerve parameters and subcutaneous depth were observed in both genders to establish normal reference values for the purpose of creating database. The association of nerve parameter to Body Mass Index (BMI) was also studied. To compare the change in a parameter at two different time intervals, paired t-test was used. To test the significance of two means, the Student’s t-test was used. Results: Amongst the total 100 subjects, 50 were males and 50 females with age range 17-25 years. Mean CSA, perimeter and DFS (depth from skin) of TN was 9.6±1.02 mm2 , 9.95±0.78 mm and 9.7±1.13 mm, respectively, whereas the DPN mean CSA, perimeter and subcutaneous depth was 8.0±1.05 mm2 , 8.5±1.12 mm and 9.0±0.98 mm, respectively. The CSA and perimeter of right TN was significantly (p-value=0.004) greater than left. DPN mean CSA (p-value=0.008) and perimeter (p-value <0.001) were significantly greater on the right side in comparison to left. The TN was significantly deeper in location in females (p<0.004). DPN was significantly deeper in females than males (p<0.001). Differences in nerve parameters among subjects in relation to were insignificant. Conclusion: Nerve parameters were conveniently measured by ultrasound. Knowledge of site-specific normal size of nerves is of great importance in diagnosing various neuropathies, compression syndromes and traumatic nerve lesions. In current study, we have attempted to create a reference database that may be valuable for neurologists as well as radiologists. Knowledge of nerve depth and location may help in guiding ankle blocks in various surgeries and for other diagnostic and therapeutic purposes.